Disruptive Innovation In Banking Sectors (International Journal of Scientific Research and Management (IJSRM), 2016)
This paper consists the current state of innovation in the financial services industries and the need for banks to embrace innovation as a key element in addressing the challenge of continuing disruptive change in technology and consumer habits. This paper also introduces the concept of Open Innovation and its most common practices and discusses opportunities for financial services organizations to adopt innovation in the corporate environment. To put open innovation practices in context for financial services organizations, relevant open innovation and the benefits of such initiatives highlighted in the financial sector.This paper consists the current state of innovation in the financial services industries and the need for banks to embrace innovation as a key element in addressing the challenge of continuing disruptive change in technology and consumer habits. This paper also introduces the concept of Open Innovation and its most common practices and discusses opportunities for financial services organizations to adopt innovation in the corporate environment. To put open innovation practices in context for financial services organizations, relevant open innovation and the benefits of such initiatives highlighted in the financial sector.